Nuclear translation - Baboo, S (2012)
In bacteria, protein synthesis can occur tightly coupled to transcription. In eukaryotes, it is believed that translation occurs solely in the cytoplasm; I test whether some occurs in nuclei and find: (1) L-azidohomoalanine (Aha) – a methionine analogue (detected by microscopy after attaching a fluorescent tag using ‘click’ chemistry) – is incorporated within 5 s into nuclei in a process sensitive to the translation inhibitor, anisomycin. (2) Puromycin – another inhibitor that end-labels nascent peptides (detected by immuno-fluorescence) – is similarly incorporated in a manner sensitive to a transcriptional inhibitor. (3) CD2 – a non-nuclear protein – is found in nuclei close to the nascent RNA that encodes it (detected by combining indirect immuno-labelling with RNA fluorescence in situ hybridization using intronic probes); faulty (nascent) RNA is destroyed by a quality-control mechanism sensitive to translational inhibitors. I conclude that substantial translation occurs in the nucleus, with some being closely coupled to transcription and the associated proof-reading. Moreover, most peptides made in both the nucleus and cytoplasm are degraded soon after they are made with half-lives of about one minute.